2015
DOI: 10.1186/s40200-015-0131-8
|View full text |Cite
|
Sign up to set email alerts
|

Kidney injury molecule-1 as a predicting factor for inflamed kidney, diabetic and diabetic nephropathy Egyptian patients

Abstract: BackgroundKidney injury molecule-1 (KIM-1), a recently discovered transmembrane protein, is expressed in dedifferentiated proximal renal tubular epithelial cells in damaged regions. Kidney injury early detection in diabetic patients has great importance for therapy and prognosis. Therefore, the aim of the present study is to predict, validate and evaluate the presence of KIM-1 in kidney inflammation, dialectic and diabetic nephropathy diseases.MethodsSixty males and females subjects (30-52 years) were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
1
11
0
3
Order By: Relevance
“…79 Previously it has been reported that KIM-1 correlate positively with the high glucose level in diabetic patients. 80 Expression of KIM-1 and NGAL reported to be increased in renal tissue of rats during DN which is consistent with the results of our present investigation. 81 Administration of LG showed significant inhibition in upregulation of diabetes-induced KIM-1 and NGAL mRNA expression, which might be due to its antihyperglycemic potential.…”
Section: Discussionsupporting
confidence: 83%
“…79 Previously it has been reported that KIM-1 correlate positively with the high glucose level in diabetic patients. 80 Expression of KIM-1 and NGAL reported to be increased in renal tissue of rats during DN which is consistent with the results of our present investigation. 81 Administration of LG showed significant inhibition in upregulation of diabetes-induced KIM-1 and NGAL mRNA expression, which might be due to its antihyperglycemic potential.…”
Section: Discussionsupporting
confidence: 83%
“…But these effects of high glucose were significantly blocked by KIM-1 siRNA, which was confirmed by the significantly decreased expression of the LC3-II (Fig. 3A and 3B) renal KIM-1 and urinary KIM-1 are significantly increased in DN patients [14,25]. However, whether KIM-1 plays a protective or injurious role in DN progression remain unclear.…”
Section: Effect Of Kim-1 Sirna On High Glucose-induced Autophagy and mentioning
confidence: 66%
“…In context, KIM-1 was significantly reduced by the GLP-1 agonist, exendin-4, in rats subjected to renal ischemia/ reperfusion injury [37]. Indeed, KIM-1 has been found to be positively correlated with hyperglycemia in diabetic patients [38].…”
Section: Discussionmentioning
confidence: 99%